Mobile English in Local Lives: Pre-Service Teachers’ Code-Switching, Polycentric Norms, and Bilingual Self-Monitoring Across Translocal Digital Spaces - Yanuarius Yanu Dharmawan; Bayu Andika Prasatyo (Journal of General Education and Humanities, 2026)
English use in EFL contexts increasingly extends beyond classrooms into digital communication and online platforms, where learners encounter multiple standards and sources of evaluation regarding what counts as “good English.” While previous studies have examined translanguaging and digital language practices, less is known about how pre-service English teachers negotiate legitimacy, confidence, and self-monitoring in everyday communication. This study explored how Indonesian pre-service English teachers use Indonesian–English repertoires across different contexts. Using a qualitative interpretive design, data were collected from eight sixth-semester English Education students through narrative questionnaires and participant-selected artifacts and analyzed using abductive thematic analysis. The findings identified four themes: audience and platform as drivers of language choice, code-switching as purposeful social action, the influence of multiple evaluative standards on confidence and participation, and bilingual self-monitoring through inhibition, rehearsal, substitution, and digital tool use. The findings suggest that teacher education programs should address not only English accuracy but also confidence, feedback culture, translanguaging practices, and digital communication awareness.